Anticoagulant use in patients with nonvalvular atrial fibrillation: has prescribing improved? - Bista, D.; Chalmers, Leanne; Peterson, G.; Bereznicki, L. (Sage Publications, Inc., 2016)
Discordance between international guideline recommendations and anticoagulant prescribing patterns among patients with nonvalvular atrial fibrillation (NVAF) has been frequently reported. This study was designed to compare the anticoagulant utilization pattern to earlier data in the same population and identify predictors of anticoagulant prescribing among patients with NVAF. We reviewed patients with NVAF admitted to Tasmania’s 3 major hospitals between January 2011 and June 2012 and compared the anticoagulant utilization pattern to earlier data. Patients were excluded if they had only 1 episode of NVAF that reverted spontaneously or upon cardioversion. Multivariate logistic regression analysis was used to identify predictors of anticoagulant prescribing. Overall, 53.8% of patients received anticoagulant treatment compared to 40.4% 15 years ago. Among eligible patients at high-risk of stroke, 52.5% were receiving anticoagulant therapy (vs 42.1% 15 years ago). Approximately 10% of patients with a CHADS2 score ≥2 were not receiving any antithrombotic treatment, reduced from 18.2% in the earlier cohort, whereas anticoagulant use increased among those at low risk (score 0) to 48.5% from 14.2%. Younger age (odds ratio [OR] 0.99, 95% confidence interval [CI] 0.97-1.0; P = .04); CHADS2 = 1, relative to 0 (OR 1.68, 95% CI 1.07-2.63; P = .02); CHF (OR 1.56, 95% CI 1.12-2.15; P = .008); and embolic disease history (OR 1.77, 95% CI 1.09-2.86; P = .02) were significant predictors of anticoagulant prescribing. While there has been improvement over the past 15 years, suboptimal use of anticoagulant therapy among high-risk patients with NVAF remains common. There is significant potential for improvement in the quality of stroke prophylaxis in patients with NVAF.